Grey Relational Analysis-Based Fault Prediction for Watercraft Equipment - Feng, Shasha; Chen, Zijian; Guan, Qunsheng; Yue, Jingtao; Xia, Chengyi (Frontiers in Physics, 2022)
In this paper, we aim to investigate the fault prediction for watercraft equipments by using grey relational analysis. At first, the healthy degree model of watercraft equipments is proposed, and then two main theorems are derived to determine the healthy condition criteria for equipments. Lastly, the relevant simulation results are provided to verify the validity and accuracy of the healthy degree model. Current results can be helpful to effectively design the supporting mode of watercraft equipment and realize the transformation of watercraft equipment support from planned maintenance to predictive maintenance.